1988
DOI: 10.1126/science.3263702
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of EGF-Dependent Cell Proliferation by EGF Receptor Kinase Inhibitors

Abstract: A systematic series of low molecular weight protein tyrosine kinase inhibitors were synthesized; they had progressively increasing affinity over a 2500-fold range toward the substrate site of epidermal growth factor (EGF) receptor kinase domain. These compounds inhibited EGF receptor kinase activity up to three orders of magnitude more than they inhibited insulin receptor kinase, and they also effectively inhibited the EGF-dependent autophosphorylation of the receptor. The most potent compounds effectively inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
266
0
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(277 citation statements)
references
References 16 publications
8
266
0
3
Order By: Relevance
“…A large majority of astrocytes were sensitive to TGFa mitogenic effects in our cultures with 80% of cells having entered the cell cycle at 3 days (Figure 5b). Finally, AG1478, a specific inhibitor of erbB1 tyrosine kinase activity (Yaish et al, 1988) abolished TGFainduced proliferation as observed at 7 DIV (percentage of BrdU-immunoreactive nuclei over total nuclei numbers labelled with hematoxylin: untreated, 18.371.8; AG1478-treated, 1171.2; TGFa-treated, 70.671; TGFa plus AG1478-treated, 13.470.8, mean7s.e.m., n ¼ 4). To evaluate the transduction pathways underlying this mitogenic effect, astrocytes were treated with TGFa in the additional presence of U0126, a specific inhibitor of both MEK1 and MEK2 kinase activities, which prevents phosphorylation, and thus activation of ERK1/2 (Favata et al, 1998).…”
Section: Resultsmentioning
confidence: 89%
“…A large majority of astrocytes were sensitive to TGFa mitogenic effects in our cultures with 80% of cells having entered the cell cycle at 3 days (Figure 5b). Finally, AG1478, a specific inhibitor of erbB1 tyrosine kinase activity (Yaish et al, 1988) abolished TGFainduced proliferation as observed at 7 DIV (percentage of BrdU-immunoreactive nuclei over total nuclei numbers labelled with hematoxylin: untreated, 18.371.8; AG1478-treated, 1171.2; TGFa-treated, 70.671; TGFa plus AG1478-treated, 13.470.8, mean7s.e.m., n ¼ 4). To evaluate the transduction pathways underlying this mitogenic effect, astrocytes were treated with TGFa in the additional presence of U0126, a specific inhibitor of both MEK1 and MEK2 kinase activities, which prevents phosphorylation, and thus activation of ERK1/2 (Favata et al, 1998).…”
Section: Resultsmentioning
confidence: 89%
“…RG 50864 belongs to a family of arylidene derivatives recently described to inhibit the tyrosine kinase activity of the EGF receptor at concentrations 1/100th to 1/700th the concentration needed to block tyrosine kinase of the insulin receptor (25). Like insulin, EGFs mechanism of action involves both autophosphorylation of its receptor and tyrosine phosphorylation of a variety of cellular target proteins (32).…”
Section: Discussionmentioning
confidence: 99%
“…In all experiments the MEs were preincubated for 15 min, then for 30 min after a change of medium, and finally for 2 h with the growth factors of interest. At the end of this period, the medium was removed and assayed for LHRH and PGE2 as reported (24 (25). The inhibitor was initially dissolved in ethanol and then diluted in the incubation medium to a final concentration of 60 ,tM, which was present throughout the entire incubation period.…”
mentioning
confidence: 99%
“…One such class of TK inhibitors, referred to as tyrphostins, was reported in the late 1980s (Yaish et al, 1988). Synthesised and developed by a team in Israel, this novel class of compounds was one of the first to demonstrate p210 BCR -ABL TK inhibitory properties, inducing cell kill in K562 cells (Anafi et al, 1993).…”
mentioning
confidence: 99%